Padrões ecológicos da comunidade de protozoários flagelados (Protista: Mastigophora) no plâncton de um sistema rio-planície de inundação tropical. - Camargo, Janielly Carvalho (2013)
Regarding the flagellate protozoa community, a scientometric study was approached, which focuses on the paths of the world scientific literature produced in fifferent types of environments, focusing primarily on researches on the ecology of these organisms. It represents one of the first major faunal surveys of the flagellate protozoa community in 36 environments (lotic, semilotic and lentic) of the Upper Paraná River floodplain and one of the first studies to identify and assess patterns of spatial distribution of this community in these environments, as well as one of the first studies to identify the factors regulating the spatial distribution of these organisms in this type of ecosystem. The number of publications on flagellate has grown significantly over the years. Altogether 445 studies were found about the flagellate; however, few studies have addressed ecological aspects of this community (only 74 publications). Most research has addressed mainly to the areas of medical interest, as immunology, biochemistry, genetics, molecular biology and parasitology. Besides that, most of the studies on the flagellates are concentrated in countries with greater economic and scientific development. The main results found in the ecological approach were: (1) The flagellate protozoa community possesses a high species diversity in the Upper Paraná River floodplain, being represented by 171 taxa. (2) The PERMANOVA showed that the patterns of density and species composition of flagellate are different between types of environments (lotic, semilotic and lentic) and between study periods (drought and flood), thus indicating that the structure of this community is influenced by the seasonality of the hydrological regime and by the hydrological connectivity of studied environments. (3) The analysis of spatial autocorrelation and the C-score index revealed that flagellate are spatially structured in environments of the Upper Paraná River floodplain, in both periods. (4) The partial redundancy analysis (pRDA) pointed out that most of the variation of attributes of the flagellate community remained unexplained (residual variation), and could not be attributed to environmental or spatial factors included in the pRDA. (5) The factors that may have structured the spatial and seasonal variation of flagellate not included in the pRDA probably are the biotic interactions (predation and/or competition) of these organisms with other microbial communities, hydrological and/or morphometric variations, climatic variations and even stochastic events. The results obtained can be used to better support planning the sampling design of studies on microorganisms in floodplains and also to guide the adoption of conservation and management strategies in these ecosystems, as it became clear that, contrary to what was traditionally postulated, not all microorganisms are widely distributed and ttherefore they also need areas targeted for conservation.